PENINGKATAN KADAR ENZIM TRANSAMINASE SEBAGAI PREDIKTOR DIABETES MELITUS TIPE 2 PADA PASIEN PERLEMAKAN HATI NON ALKOHOLIK-LITERATURE REVIEW - Hanny Mutiarayni Balga (2020)
Background : Type 2 Diabetes Mellitus (DM) and Non Alcoholic Fatty Liver Disease (NAFLD) is one of the most common metabolic disease in the world. Previous studies states that there is a relationship between DM type 2 and NAFLD. There is a lot of factor that influence of developing DM type 2 one of them is transaminase enzyme. We aimed to know whether elevation of transaminase enzyme in NAFLD patient can be one of the predictor type 2 DM. Methods: This study is using a systemativ review and keywords (NAFLD OR Non Alcoholic fatty liver disease) AND (Liver enzyme OR hepatic enzyme OR transaminase OR alanine aminotransferase OR aspartate aminotransferase) AND (risk of diabetes type 2 OR incidence of diabetes type 2) reported in PRISMA -P 2015. The database for this literature search is PubMed and Science Direct and synthesis methods using a PICO. This systematic review appraisal study uses the Critical Appraisal Skills Program (CASP) 2018. Results : There is a relationship between the incidence of NAFLD and the risk of incidence of type 2 diabetes and an increase in the levels of the transminase enzyme in NAFLD patients is one of the risk factors for the incidence of type 2 diabetes. Conclusion : Our result indicate that the increase in transaminase enzyme levels both ALT and AST was one of the predictor of the incidence of type 2 DM in NAFLD patients.